Evaluation of Anterior Chamber Volume in Cataract Patients with Swept-Source Optical Coherence Tomography - Wenwen He; Xiangjia Zhu; Don Wolff; Zhennan Zhao; Xinghuai Sun; Yi Lu (Journal of Ophthalmology)
Purpose. To evaluate the anterior chamber volume in cataract patients with Swept-Source Optical Coherence Tomography (SS-OCT) and its influencing factors. Methods. Anterior chamber volume of 92 cataract patients was evaluated with SS-OCT in this cross-sectional study. Univariate analyses and multiple linear regression were used to investigate gender, age, operated eye, posterior vitreous detachment, lens opacity grading, and axial length (AXL) related variables capable of influencing the ACV. Results. The average ACV was 139.80 ± 38.21 mm3 (range 59.41 to 254.09 mm3). The average ACV was significantly larger in male patients than in female patients (P=0.001). ACV was negatively correlated with age and LOCS III cortical (C) grading of the lens (Pearson’s correlation analysis, r=-0.443, P<0.001, and Spearman’s correlation analysis, ρ=-0.450, P<0.001). ACV was also increased with AXL (Pearson’s correlation analysis, r=0.552, P<0.001). Multiple linear regression showed that, with all of the covariates entered into the model, gender (P=0.002), age (P=0.015), LOCS III C grade (P=0.043), and AXL (P=0.001) were still associated with ACV (F=10.252  P<0.001  R2=0.498). Conclusion. With SS-OCT, we found that, in healthy cataract patients, ACV varied significantly among different subjects. Influencing factors that contribute to reduced ACV were female gender, increased age, LOCS III C grade, and shorter AXL.